Studying molecular quantum dynamics with the multiconfiguration time-dependent Hartree method - Meyer, Hans-Dieter (Wiley interdisciplinary reviews. Computational Molecular Science, 2012)
This review covers the multiconfiguration time-dependent Hartree (MCTDH) method, which is a powerful and general algorithm for solving the time-dependent Schrödinger equation. The formal derivation is discussed as well as applications of the method. Recent extensions of MCTDH are treated in brief, namely, MCTDHB and MCTDHF, for treating identical particles (bosons and fermions), and the very powerful multilayer (ML-MCTDH) formalism. Compact representations of potential energy surfaces (PESs) are also discussed, as the representation of a PES becomes a major bottleneck when going to larger systems (nine or more dimensions) while employing a full-dimensional, complicated, and nonseparable PES. As applications of MCTDH, we discuss the calculation of photoionization and photoexcitation spectra of the vibronically coupled systems butatriene and pyrazine, respectively, and the infra-red spectrum of the Zundel cation (protonated water dimer) H5O+2. © 2011 John Wiley & Sons, Ltd. This article is categorized under: Theoretical and Physical Chemistry > Reaction Dynamics and Kinetics
Gesehen am 28.11.2018